The impact of sowing time on vegetative characteristics of winter wheat in Poltava region - Kobylynska, О. (Scientific Progress & Innovations, 2023)
The research was conducted concerning the study of the manifestation level of soft winter wheat vegetative plant part depending on sowing time in Poltava region. The investigation was conducted during 2019‒2020 in laboratory and field conditions of the Training and Production Center of Selection and Seed Growing of Field Crops at Poltava State Agrarian University (Poltava district).75 samples of varieties and selection lines of soft winter wheat (Triticum aestivum L.) bred in Poltava State Agrarian University and other selection establishments were taken as material for the research. Soft winter wheat samples were studied according to the following vegetative characteristics: plant height; straw thickness of the second internode; the amount of internodes; the length of the upper and lower inter-nodes; ear length; plant and stem weight. Conducting general characteristics of the properties as to forming the signs of vegetative organs and their variability, it is necessary to note that, of course, they change under the influence of stressful climatic conditions. Moreover, some characteristics preserve definite conformities to natural laws that can be used in the modern technology of the selection process in order to raise plant yield capacity under climate change. It has been proven that different sowing time had inconsiderable effect on the formation of the following character-istics: straw thickness of the second internode, the amount of internodes, ear length, and stem weight. So, they are genetically determined and under late sowing time have reserves for the search and selection of genotypes by more straw thickness of the second internode, larger ear length, the optimal number of internodes, and stem weight. It has also been determined that at late sowing time the length of the upper and lower internodes inconsiderably decrease their level of formation, and plant weight, on the contrary, increases it. The obtained information is important in the selection process of soft winter wheat, as well as in studying the parent material and planning hybridizations.